2018
DOI: 10.1177/2158244018801097
|View full text |Cite
|
Sign up to set email alerts
|

To Be Accountable While Showing Care: The Lived Experience of People in a Servant Leadership Organization

Abstract: Many organizations attribute their success to the use of servant leadership. However, very few studies have been conducted with the emphasis of understanding what it is like for people to work in servant leadership organizations and how it is practiced. Thus, in-depth interviews were conducted and an observation was performed to explore the lived experience of people, both employees and managers, who work within the business sector where servant leadership has been practiced for decades. Two main themes (and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
1
23
0
4
Order By: Relevance
“…In the views of Russell and Gregory Stone (2002), van Dierendonck (2011), and Parris and Peachey (2013), servant leaders look for a higher plane of operation, and their prime motivation in leadership is their desire to serve their followers. Both dimensions of servant leadership "to serve" and "to lead" are important for prosperity of an organization (Ragnarsson et al, 2018). According to Sendjaya and Sarros (2002), "the servant leader operates on an assumption that 'I am the leader, therefore I serve' rather than 'I am the leader, therefore I lead'" (p. 60).…”
Section: Servant Leadershipmentioning
confidence: 99%
“…In the views of Russell and Gregory Stone (2002), van Dierendonck (2011), and Parris and Peachey (2013), servant leaders look for a higher plane of operation, and their prime motivation in leadership is their desire to serve their followers. Both dimensions of servant leadership "to serve" and "to lead" are important for prosperity of an organization (Ragnarsson et al, 2018). According to Sendjaya and Sarros (2002), "the servant leader operates on an assumption that 'I am the leader, therefore I serve' rather than 'I am the leader, therefore I lead'" (p. 60).…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Pilar Dinamika Integra. This company is proof that SMCC not only encourage their members to find their purpose of life, but also help to provide the vision of their members (VJ) in the marketplace (Byfield, 2008;Ragnarsson, 2018). By helping VJ found this business, SMCC is encouraging him to be free from financial pressure (Chandra, 2017).…”
Section: The True Successmentioning
confidence: 93%
“…It can be observed that the vast majority of SL articles reviewed (125 out of 179) explored the effect of servant leadership on a broad range of positive and negative employee outcomes. The positive employee outcomes included employee commitment (e.g., Cerit, 2010;Bobbio et al, 2012;Harwiki, 2016;Newman et al, 2018;Erdurmazli, 2019), employee motivation (e.g., Schwarz et al, 2016;Tuan, 2016;Shim and Park, 2018), organizational citizenship behaviour (e.g., Abu Bakar and McCann, 2016;Bavik et al, 2017;Linuesa-Langreo et al, 2018;Ragnarsson et al, 2018;Zhu and Zhang, 2019), employee well-being (Chen et al, 2011;Chughtai, 2018;Yang et al, 2018;Chughtai, 2019;Mustard, 2019), job satisfaction (Al-Mahdy et al, 2016;Abu Bakar and McCann, 2018;Farrington and Lillah, 2018;Megheirkouni, 2018;Al-Asadi et al, 2019), proactive behaviour (Bauer et al, 2019) and trust in leader (Chan and Mak, 2014) . The negative employee outcomes included employee burnout (Babakus et al, 2010;Rivkin et al, 2014) and turnover intentions ((Babakus et al, 2010;Kashyap and Ragnekar, 2014;Brohi et al, 2018).…”
Section: Sl Themesmentioning
confidence: 99%